Instruments of violence: Female suicide bombers of Boko Haram - Galehan, Jordan (International journal of law, crime and justice, 2019)
Groups engaging in political violence are utilizing women more frequently in operational roles, with females as suicide bombers being the most common role of women in terrorist attack events. In recent years, the trend in female suicide bombers has spiked and sources indicate that this can be attributed to the Boko Haram group in the Sub-Saharan Africa region, which has utilized more women as suicide bombers than any other group in history. Therefore, the present study seeks to address potential reasons for the high levels of women's involvement in suicide attacks by Boko Haram. Results of content analysis of publicly available, open-sourced media materials cited in the Global Terrorism Database suggests that women engaging in suicide bombing events affiliated with Boko Haram are being used as instruments for the group's violent objectives.